Keberhasilan Program Makan Bergizi Gratis di Jawa Barat Tahun 2026: Tinjauan Literatur Scoping - moh sadli; Lili Amaliah (Jurnal Kesehatan Mahardika, 2026)
Introduction: The Free Nutritious Meals Program (MBG) is a national priority program intended to improve human resource quality through nutrition fulfillment for schoolchildren and other vulnerable groups. Purpose: This study aimed to analyze the factors determining the success of MBG implementation in West Java Province in 2026. Design/methods/approach: A scoping literature review was conducted using a structured search of books, technical guidelines, laws, presidential regulations, government policy documents, health profiles, international reports, and national and international journals related to school feeding, nutrition governance, food safety, policy implementation, and regional health systems. Findings/results: The success of MBG in West Java is determined not only by food availability, but also by governance clarity, targeting accuracy, human resource capacity, menu quality, food safety, SPPG effectiveness, integration with Puskesmas and Posyandu, multisectoral coordination, local government support, local supply chains, and data-based monitoring and evaluation. Conclusions: MBG success should be measured using input, process, output, outcome, and food safety indicators, rather than the number of meals distributed alone.